The death cure - Dashner, James, 1972- (London : The Chicken House, 2012)
In a final effort to complete the blueprint for the cure, Thomas must rely on the Gladers, with full memories restored, but Thomas does not trust Wicked and he remembers much more than they realize.
Young Adult.
Young Adult
Keywords: Science -- Experiments -- Juvenile fiction; Survival -- Juvenile fiction; Science fiction; Science -- Experiments -- Fiction; Survival -- Fiction; Science fiction; Science -- Experiments -- Fiction; Survival skills -- Fiction; Science fiction